AB0263 ASSOCIATED FACTORS OF RESIDUAL SYMPTOMS AMONG PATIENTS WITH RHEUMATOID ARTHRITIS IN REMISSION OR LOW DISEASE ACTIVITY. (June 2019) - Kashiwagura, Takeshi; Kobayashi, Moto; Urayama, Masakazu; Konishi, Natsuo; Aizawa, Toshiaki; Itoh, Hiroki; Sugimura, Yusuke; Kawano, Tetsuya; Aonuma, Hiroshi; Sakuraba, Tsutomu; Tani, Takayuki; Abe, Hidekazu; et al.
Abstract : Background: Treatment outcomes for rheumatoid arthritis (RA) have been improved by advances in drugs. In daily clinical practice, treatment outcomes are assessed with both inflammatory findings and based on swollen joints (SJ), tender joints (TJ), a patient's global assessment on visual analogue scale (GVAS) score, a physician's GVAS score, etc. Although composite measures indicate suppressed inflammatory or articular symptoms, many patients show no improvement in GVAS scores. The reported residual symptoms include morning stiffness (MS), pain (P), and dullness (D). Objectives: We investigated the residual symptoms of patients achieving low disease activity (LDA) or complete remission (CR). Methods: His study included 111 RA patients who received outpatient treatment at our department (31 men and 80 women). The mean age was 65.1 (range, 27–89) years. The disease stages were distributed as follows: 36 patients with Stage 1, 23 patients with Stage 2, 20 patients with Stage 3, and 32 patients with Stage 4. The severity of dysfunction was distributed as follows: Class 1 in 73 patients, Class 2 in 25 patients, Class 3 in 11 patients, and Class 4 in 2 patients (Steinbrocker classification). Based on the disease activity score in 28 joints using the erythrocyte sedimentation rate, disease activity was graded as CR in 54 patients, LDA in 19, moderate disease activity in 37, and high disease activity in 1. Questionnaire forms were used to assess the presence or absence and duration of MS and the presence or absence and severity of P (Pain VAS) and of D (Dullness VAS). These variables were assessed to determine how they were associated with clinical outcome measures, drugs, and surgery. Results: The following residual symptoms were observed in 73 patients who achieved the treatment target of LDA or CR: MS in 34 patients (46.6%), P in 48 (65.6%), and D in 38 (52.8%). In the LDA+CR group, the Pain VAS (P < 0.001, r = 0.612) and Dullness VAS (P = 0.0131, r = 0.193) were significantly correlated with the GVAS. In patients with P in the LDA+CR group, the use rates for analgesics (P = 0.0047) and biological disease-modifying antirheumatic drugs (bDMARDs) (P = 0.0295) were significantly higher. In the LDA+CR group, Dullness VAS scores were significantly improved by the use of bDMARDs (P = 0.0074). No association was observed between surgical interventions (42 patients) and residual symptoms. Conclusion: Residual symptoms were frequently observed even in patients achieving LDA or CR, which is regarded as the treatment target. Because P and D were significantly correlated with the GVAS, relief of these residual symptoms is expected to improve treatment effects. Although D was relieved by bDMARDs, further studies on the treatment of residual P in patients achieving LDA or CR are necessary. Disclosure of Interests: None declared